(untitled) (Development Service Industry Management, 2023)
The purpose of the article is to consider possible variants of the criteria for optimizing resource capabilities of enterprises. Optimizing the use of resources makes it possible to reduce enterprise costs and thereby increase the overall productivity and efficiency of the enterprise. Also, improving the management of resources, in particular unique ones, allows to increase the company’s income due to the implementation of its competitive advantages. The article proposes to use the term "optimization of resources" to reflect the dependence between the amount of resources spent and the level of achievement of the company’s goals. In accordance with the above interpretation, directions for optimizing the use of resources are determined. It is proposed to include measures aimed at optimizing their quantity, quality, organization of provision and management. Resource management is proposed to be subordinated to enterprise development management. The article analyzes the key aspects of enterprise development management as a guideline for resource management. Activities aimed at optimizing the resource capabilities of enterprises must be based on compliance with certain criteria. Application of such criteria helps to monitor the correspondence of the existing and desired state of the management object. The possibilities of applying the criteria of "resource conservation", "rationality" and "maximization of enterprise value" as criteria for optimizing the management of resource capabilities of enterprises are analyzed. Resource conservation should be considered as one of the main parameters of managing resource opportunities, which is due to humanity’s awareness of the problems associated with the depletion of natural resources. The rationality parameter allows you to combine resource saving with obtaining goods of the appropriate quality. It is noted that each of the specified criteria should reflect the level of achievement of the company’s development goals thanks to the use of the available level of resources.